Osadzeni z niepełnosprawnością fizyczną — w kierunku diagnozy potrzeb - Nymś-Górna, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Among the prison population in Poland there are also people with disabilities. The text will focus on physical disability. Convicts with physical disabilities constitute a group that, in penitentiary reality, is faced with many difficulties. Specialised interactions should be directed towards them. Prison Service officers try to minimise factors that may adversely affect the functioning of people with physical disabilities in prisons and pre-trial detention centres. The purpose of this article is to draw attention to prisoners with a physical disability and the specificity of their needs in penitentiary units.
Keywords: inwalidztwo; więzienie; przestępca; izolacja; system terapeutyczny